Ефектите од странските директни инвестиции во земјите во транзиција, со посебен осврт на Република Македонија - Таст, Јелена (Економски факултет, УКИМ, Скопје, 2014)
The PhD thesis is organized into four parts complementing each other and together with the introduction and the conclusion and recomendations they present in a logical order the contents of the theoretical and practical research. The research paper's basic hypothesis is that the effect of FDI on the economic development depends on the absorption capacities of the relevant countries, which are related to the FDI inflow determining factors. In this context, the focus of the research is directed towards the link between the FDI effects and the absorbing capacity of the transition countries related to the determinants of FDI. In this context, an analysis has been made of the macroeconomic effects of FDI in the countries of Southeast Europe and the Commonwealth of Independent States. In this context, the research of the FDI effects in the transition countries evaluates the validity of the FDI determinants. The paper researchs FDI motives, determinants and effects in the Republic of Macedonia. The first chapter summarizes the theoretical aspect of the motives for capital export in the form of FDI in order to analyze the causality on the FDI flow from developed countries into transition countries. The second chapter analyses the FDI inflow and structure, and motives and determinants of FDI in Southeast European Countries and the Commonwealth of Independent States through the scientific and empirical analysis supported by quantitative data. The third chapter examines the macroeconomic effects of FDI in the countries of Southeast Europe and the Commonwealth of Independent States in the period 2004-2011 through a statistical analysis of the linear regression correlation of the relevant economic variables. In this context the paper analyze the relationship between FDI and economic growth in transition economies. The fourth chapter research the conditions related to the FDI in the Republic of Macedonia. An empirical research in the form of a questionnaire has been carries out which served as an initial framework in defining the future directions of the FDI related policies in the Republic of Macedonia.
The foreign direct investment effects in transition economies, with highlights on Republic of Macedonia
Докторска дисертација одбранета во 2014 година на Економскиот факултет во Скопје, под менторство на проф. д–р Љубица Костовска.